Number of pigs per pen with equal space per pig - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Groups of 6, 12, or 24 pigs averaging 37 pounds each were assigned to pens where each pig had 3.85 square feet of floor space for a 4-week feeding period. Pigs in groups of 12 gained significantly slower and showed a much higher incidence of tail-biting than groups of 6 or 24. Feed efficiency was similar for all groups. In groups of 12 three pigs per feeder space gave the same results as six pigs per feeder space.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Feed efficiency; Floor space